Exports, University-Industry Linkages, and Innovation Challenges in Bangalore, India - D'Costa, Anthony P. (World Bank, Washington, DC, 2012)
The success of the Indian software industry is now internationally recognized. Consequently, scholars, policymakers, and industry officials everywhere generally anticipate the increasing competitiveness of India in high technology activities. Using a structural framework, the author argues that Bangalore's (and India's) information technology (IT) industry is predicated on an Indian business model which does not encourage thick institutional linkages such as those encapsulated by the triple helix model. Under this institutional arrangement there is cross-fertilization of new ideas and new modes of institutional interaction between industry, academia, and government. Though there are several hundred IT businesses in a milieu of numerous engineering and science colleges and high-end public sector research institutes, the supposed thick institutional architecture is in reality quite thin. This is due to a particular type of an export-oriented model which is based on off-shore development of software services, targeted mainly to the United States. Neither domestic market nor non-U.S. markets such as East Asia are pursued aggressively by Indian firms, which offer alternative forms of learning. Consequently, Bangalore's dynamism in the IT industry stems from linear and extensive growth rather than nonlinear and intensive growth. The author argues that Bangalore has serious innovation challenges with weak university-industry linkages, lack of inter-firm collaboration, and the absence of cross-fertilization between the knowledge-intensive defense/public sector and the commercial IT industry. To strengthen Bangalore's and India's innovation system, the Indian business model must be reformed by diversifying geographical and product markets, stemming international and internal brain drain, and contributing to urban infrastructure.